Regional importance and potential of Passiflora: the case of the Yucatan Peninsula and Chiapas, Mexico - Omar Franco-Mora; Jesús Ricardo Sánchez-Pale; Álvaro Castañeda-Vildózola; José Alfredo Moreno-Jiménez (Technology in Horticulture)
According to Mexican herbaria, scientific databases, and literature, 91 Passiflora species are registered in Mexico; thus, worldwide, this country presents the fifth largest diversity for this genus. Among Passiflora species, the most important economic species include yellow and red passion fruit (Passiflora edulis). In southern Mexico, in Campeche, Chiapas, Quintana Roo, and Yucatán states, 50% of the countries Passiflora diversity are recorded. Fifty-five Passiflora species have been recorded, 50 in Chiapas, 23 in Quintana Roo, 22 in Campeche, and 17 in Yucatán. At the municipality level, Ocosingo, Chiapas, presented the highest number of Passiflora species of 21; followed by Othón P. Blanco, Quintana Roo, with 14; and Calakmul, Campeche, with 11. In its territory, Chiapas presents five biogeographical regions, explaining, at least in part, its richness in Passiflora species. The fruits of several species of this genus have been used in local communities as food, mainly beverages, and traditional medicine.